Comparative Assessment of Manual Paddy Drum Seeders - Baruah, D C (Journal of Agricultural Engineering, 2009)
The present investigation was carried out to test the feasibility as well as to assess comparative performance of four different drum type direct sowing devices for paddy. The results of the experiment indicated that mechanical drum seeders ensured increase in field capacity resulting in saving in time compared to manual line sowing. Amount of man-hour saving varied within a range of 78% to 95% over the manual sowing, the highest saving obtained for a commercial plastic made drum seeder. The saving of man-hour was negatively correlated with the machine weight. The lighter weight (8.00 kg) and simpler construction were the main reason of speedy operations of plastic drum seeder with highest amount of man-hour saving (95%). Variations of plant population and grain yield were found statistically insignificant amongst the seeding treatments.